2013
DOI: 10.1364/oe.21.005255
|View full text |Cite
|
Sign up to set email alerts
|

Influence of large permanent dipoles on molecular orbital tomography

Abstract: The influence of large permanent dipoles on molecular orbital tomography via high-order harmonic generation (HHG) is investigated in this work. It is found that, owing to the modification of the angle-dependent ionization rate resulting from the Stark shift, the one-side-recollision condition for the tomographic imaging can not be satisfied even with the few-cycle driving pulses. To overcome this problem, we employ a tailored driving pulse by adding a weak low-frequency pulse to the few-cycle laser pulse to co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This feature of HHG helps people better understand the microscopic world. For example, the electronic orbitals of molecules can be imaged with subfemtosecond resolution using amplitudes and phases of high harmonics [27][28][29][30]. In addition, the chiral HHG method paves a way to probe the molecular chirality on a subfemtosecond time scale [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…This feature of HHG helps people better understand the microscopic world. For example, the electronic orbitals of molecules can be imaged with subfemtosecond resolution using amplitudes and phases of high harmonics [27][28][29][30]. In addition, the chiral HHG method paves a way to probe the molecular chirality on a subfemtosecond time scale [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, HHG has been intensively investigated for its potential applications in experimentally generating a coherent attosecond pulse [1,2] in the extreme ultraviolet (XUV) and soft x-ray regions [3]. The availability of isolated attosecond pulses has successfully opened new research areas for probing ultrafast processes of physics, chemistry and biology with unprecedented temporal and spatial resolutions [4][5][6][7][8][9][10][11]. For example, it has been shown that an attosecond XUV pulse can be used to study inner-shell electron dynamics in atoms and molecules [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These results are due to the symmetry property of the orbitals and the feature of the inverse Fourier transform in the limited k-space. Besides the above discussed orbitals with symmetry or antisymmetry, the orbital can also be nonsymmetrically distributed, the reconstruction of which was discussed in [18].…”
mentioning
confidence: 99%
“…Besides the above discussed orbitals with symmetry or antisymmetry, the orbital can also be nonsymmetrically distributed, the reconstruction of which was discussed in [18].…”
mentioning
confidence: 99%